2012
DOI: 10.2136/sssaj2011.0361
|View full text |Cite
|
Sign up to set email alerts
|

Short, Multineedle Frequency Domain Reflectometry Sensor Suitable for Measuring Soil Water Content

Abstract: Time domain reflectometry (TDR) is a well‐established electromagnetic technique used to measure soil water content. Time domain reflectometry sensors have been combined with heat pulse sensors to produce thermo‐TDR sensors. Thermo‐TDR sensors are restricted to having relatively short needles to accurately measure soil thermal properties. Short needle lengths, however, can limit the accuracy of the TDR measurement of soil water content. Frequency domain reflectometry (FDR) sensors are an alternative to TDR sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
(56 reference statements)
2
15
0
Order By: Relevance
“…The short physical probe length of a thermo‐TDR sensor also limits the accuracy of soil water determination. A possible alternative is to use a thermo‐FDR (Sheng et al, ), because capacitance or impedance sensors (FDR) allow more flexibility in electrode configuration with reduced measurement complexity compared to TDR, in addition to lower costs of the electronics system and minimal postprocessing (Sheng et al, ; Xu et al, ; Zent et al, , ). Sheng et al () coupled an electromagnetic sensor to determine water content with a penta‐needle thermo‐FDR, which demonstrated a significant improvement in soil water content determination (with RMSE = 0.012 cm 3 /cm 3 compared to RMSE = 0.042 cm 3 /cm 3 of the HP methods).…”
Section: Limitations and Perspectives Of The Hp Methodsmentioning
confidence: 99%
“…The short physical probe length of a thermo‐TDR sensor also limits the accuracy of soil water determination. A possible alternative is to use a thermo‐FDR (Sheng et al, ), because capacitance or impedance sensors (FDR) allow more flexibility in electrode configuration with reduced measurement complexity compared to TDR, in addition to lower costs of the electronics system and minimal postprocessing (Sheng et al, ; Xu et al, ; Zent et al, , ). Sheng et al () coupled an electromagnetic sensor to determine water content with a penta‐needle thermo‐FDR, which demonstrated a significant improvement in soil water content determination (with RMSE = 0.012 cm 3 /cm 3 compared to RMSE = 0.042 cm 3 /cm 3 of the HP methods).…”
Section: Limitations and Perspectives Of The Hp Methodsmentioning
confidence: 99%
“…A third-order polynomial equation fit the data well: indicating that the dielectric dispersion frequency may be used to estimate soil water contents for different soils at different temperatures. The root mean square error (RMSE) of the q estimated by the f d measurement is 0.021, which is better than 0.027, the RMSE of q estimated at 70 MHz (Xu et al, 2012) and better than the RMSE of f d = 0.0288, which is estimated by the Topp equation.…”
Section: Resultsmentioning
confidence: 77%
“…From the complex permittivity spectra of the soils, we can determine the ideal measurement frequency at which the apparent permittivity of the four soils was relatively constant for a range of texture and temperatures. Xu et al (2012) reported that 70 MHz was the best measurement frequency at which the apparent permittivity of four select soils did not change for a range of temperatures and salinities. It should be noted that fixed-frequency methods have limitations for soil water content measurements fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations